Comparative Analysis Of The Concepts Of Ju'?lah And Maisir From The Perspective Of Fiqh Muamalah - Budan Sani; M. Fauzan Januri; Ayi Yunus Rusyana (Doctoral Program of Social Science Pasundan University, 2026)
This study aims to provide a comprehensive comparative analysis of the concepts of ju'?lah and maisir within the framework of Islamic jurisprudence (fiqh mu'?malah), focusing on their ontological, normative, and applicative dimensions in contemporary economic practices. These two concepts are often partially understood, whereas in modern economic realities—particularly within digital systems, reward-based economies, and probability-driven incentive mechanisms—they tend to overlap in interpretation. Ju'?lah, as a permissible contract in Islamic law, is characterized by the provision of rewards for achieving uncertain outcomes, yet it remains grounded in productive effort and the pursuit of public benefit (ma?la?ah). In contrast, maisir is strictly prohibited due to its inherent elements of excessive uncertainty (gharar f??ish), speculation, and exploitative gain at the expense of others. This research employs a qualitative approach using a library research method, analyzing primary sources from classical fiqh literature alongside contemporary works in Islamic economics. The analytical framework is based on descriptive-analytical and comparative methods, examining both concepts through the lenses of objectives (maq??id al-shar?'ah), transactional mechanisms, and socio-economic implications. The findings reveal that although both ju'?lah and maisir involve elements of uncertainty, they differ fundamentally in their contractual structure, value orientation, and impact on economic justice. Ju'?lah aligns with the principles of maq??id al-shar?'ah, particularly in the protection of wealth (?if? al-m?l) and the promotion of productive economic activities, whereas maisir contradicts these principles by fostering speculative behavior and unjust wealth distribution. In the context of the digital economy, this study underscores the necessity of a fiqh approach that is not merely textual but also substantive and contextual, in order to clearly distinguish between Shariah-compliant practices and prohibited activities. Therefore, this research contributes theoretically to the development of contemporary Islamic jurisprudence while also providing a normative foundation for formulating adaptive Shariah economic policies in response to evolving global trends.